FUNGSI MEDIA MASSA DALAM MENCERDASKAN KEHIDUPAN BANGSA (FUNGSI SOSIALISASI NILAI - NILAI) - Kertopati, Ton; Ratam, Waluyo (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2008)
What keeps the Indonesian Mass - Media for developing its function that it canbecome?The answer to this question is quite evident of the problems that perenniallybeset the Indonesian Mass - Media primary by the political constrains and controversies. Whiter old and new, big or small high quality and low certainly un even.In Indonesia the development of Mass communication is showinq meaningfulprogress.The main goal of tormet education in communication principles changed, and the scope of the study goes beyond the Mass - Media, other aspects such as Interpersonal communications.Group and Social etc. have to be consideredLast but not least is the Trans cendental Communication to meet ever increasingneed for socializing the National Indonesian ideology